Quo Vadis Sport Law: Pertanggungjawaban Pidana atas Kematian Suporter Sepak Bola - Galih Raka Siwi; Hana Faridah (Faculty of Law, Andalas University, 2022)
The death of supporters due to Indonesian football is not the first time. The death was caused by being trampled or squeezed by other supporters in the stadium due to the overcapacity of the stadium. This research is expected to be a reference and reference and answer the anxiety of the community, especially the alination of Indonesian football regarding accountability or even legal protection of supporters at Indonesian football matches. The Disciplinary Commission has mandated that the organizers prepare to ensure the comfort and peace of all parties including supporters both inside and around the stadium, this is part of the responsibility and obligation of the match organizers. Article 54 of the Law on Justice lists the right of spectators to be guaranteed comfort and safety. Article 359 of the Criminal Code provides criminal sanctions against parties suspected of negligence that caused death. These provisions are a form of legal protection for Indonesian football supporters. This article is discussed using a statute approach and a conseptual approach with a doctrinal (normative juridical) type of research with primary law material, secondary law material dan tertier law material.